Uremic Cardiomyopathy - Umer, Amna; Khan, Muhammad Azhar Waheed; Javed, Maryam; Khan, Azhar Ali (Pakistan Journal of Kidney Diseases, 2021)
Chronic Kidney Disease (CKD) affects approximately 10% of the general population. CKD itself is a risk factor for cardiovascular mortality and morbidity. Large epidemiological studies have clearly established a clear relationship between severity of CKD and cardiovascular event rates. Sudden cardiac death accounts for approximately 40% mortality in dialysis patients and it is usually secondary to an underlying cardiomyopathy, with left ventricular hypertrophy mostly evident on echocardiography. Several risk factors play an important role in pathogenesis of uremic cardiomyopathy including vitamin D deficiency, secondary hyperparathyroidism, phosphate retention, increased FGF23 and decreased Klotho levels. The mortality due to cardiovascular events in early stage CKD is relatively higher in comparison to progression to ESRD, so early diagnosis and treatment with dialysis should be focused.